A BAD TEACHER AND THE BEST KING IN ELISABETH HAND’S ANNA IN THE KING - Raditiyanto, Satria (Jurnal TEDC; Vol 10 No 1 (2016): Jurnal TEDC, 2019)
Deconstruction approach theory is a critical outlook concerned with the relationship between text and meaning. It also as a strategy of rules for reading, interpretation, and writing. Deconstruction approach considers that language hasn’t a definite meaning or certain. Deconstruction essentially is a way how to read a text that subvert the notion (if it is only implicitly) that text has a foundation in the language system applicable to affirm the structure, wholeness, and meaning that has been stabilized (Abrams, 1981: 38). Deconstructive readings, in contrast, treated works of art not as the harmonious fusion of literal and figurative meanings, but as instances of the intractable conflicts between meanings of different types. There is no idiom or linguistic forms meaning certain and definite. Deconstruction approach attacked the assumption that these structures of meaning were stable, universal, or a historical. This study was designed by using qualitative research model. Anna and the King novel will be analyzed by means of deconstruction approach with the title of my study : A Bad Teacher and the Best King In Elisabeth Hand’s Anna and the King. My study are deconstruction research may consider by the multiple meanings of key words in a text, etymological relationships between words, and even puns to show how the text speaks with different (and often conflicting) voices (Balkin 1990b; Balkin 1989). This analysis according to the deconstruction analysis although it has been asserted that poststructuralism (in this case deconstruction is not an applicable method). I am sure it is possible to apply some basic deconstructive moves to Elisabeth Hand text, which seems especially receptive, given its overt oppositions and emphasis on language Key words: deconstruction approach theory, Anna and the King novel, qualitative research, post-structuralism.